(untitled) (ABDIMAS: Jurnal Pengabdian Masyarakat, 2022)
Leprosy is an infectious disease that causes very complex problems, not only physical health problems but also stigma problems. Stigma delays diagnosis and treatment so that patients who come to health workers already experience disability. The government’s efforts to increase the early detection of leprosy, one of which is the intensified case finding/ICF. So the purpose of this community service is to analyze the findings of leprosy patients with ICF. The materials used in this community service are cotton, family survey form (SSF), promotional materials, and IEC teaching aids. The target of this activity is the community in RW 03 and RW 04, Tuk Village, Kedawung Health Center, Cirebon Regency. The methods used are: coordination, interview, and examination. Data analysis with univariate analysis. The results of this community service were: the achievement of finding cases of leprosy was by the target, there were no leprosy suspects found, and several other skin health problems were found, such as itching, scabies, and tinea versicolor. There should be an increase in informal education for leprosy programmers, increasing outreach efforts and the community should be able to recognize the early symptoms of leprosy.